Outcome of Anterior Cervical Discectomy and Fusion in Single Level Cervical Disc Prolapse - Sangoli, Shashank (Nepal Journal of Neuroscience, 2020)
Background: Cervical disc disease and spondylosis is a common pathological entity and is characterised by increasing degeneration of the intervertebral disc with subsequent changes in the bones and soft tissues.Aim: To determine functional outcome of anterior cervical discectomy with fusion and plating in single level degenerative cervical disc prolapse.Methods and Materials: This study was done at the Department of Neurosurgery, Medical Trust Hospital, Kochi over a period of three years after receiving institutional ethical clearance. 60 patients aged between 20 to 60 years, both male and female, who had degenerative disc disease with single level herniation with worsening or non-improving neck pain with radiculopathy, corresponding neurologic deficit, who were admitted in our unit were included in the study. Baseline data like name, age and gender were recorded for all the patients included in the study. Clinical examination consisted of history, thorough neurological examination and corresponding radiological evaluation. A visual analogue scale was used to make a subjective assessment of the patient’s complaints (pre-operative and post-operative).Results: A total of 60 patients were included in the present study, among them 40 were males and 20 were females with male to female ratio of 2:1. All of them showed a significantly better improvement in visual analogue scale score of neck pain and UE radicular pain (p